2020
DOI: 10.24018/ejbmr.2020.5.4.351
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effects of Customer Satisfaction in the Relationship between ATM Service Quality and Customer Loyalty – A Case Study from Bank of Kigali

Abstract: The current competition from both national and international markets has created a new assignment for companies to give serious consideration to providing a high quality of service to satisfy and maintain customers. This paper aimed to analyze the effects of ATM service quality on customer satisfaction and customer loyalty. The Bank of Kigali has been chosen as a case in this research. For this investigation, primary data was collected from 284 respondents from Bank of Kigali through a structured questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…(Al-Azzam, 2015;Alexis & Chen, 2019;Chandra, 2023). Customers always try to compare what they receive to their expectations or service quality needs with service quality dimensions (Nshimiyimana, 2020); therefore, it is important to know what a bank has to deliver to its customers (Octaviani et al, 2019). In the banking sector, banks must achieve service quality and customer satisfaction to remain competitive through ATMs (Alexis & Chen, 2019).…”
Section: Impact Of Atm Service Quality On Customer Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Al-Azzam, 2015;Alexis & Chen, 2019;Chandra, 2023). Customers always try to compare what they receive to their expectations or service quality needs with service quality dimensions (Nshimiyimana, 2020); therefore, it is important to know what a bank has to deliver to its customers (Octaviani et al, 2019). In the banking sector, banks must achieve service quality and customer satisfaction to remain competitive through ATMs (Alexis & Chen, 2019).…”
Section: Impact Of Atm Service Quality On Customer Satisfactionmentioning
confidence: 99%
“…The studies conducted by Krishnamoorthy (2016), Al-Azzam (2015), Alexis and Chen (2019), Lwin (2019), Indrayani et al (2019), Octaviani et al (2019), Nshimiyimana (2020), Tadesse and Bakala (2021), Elifneh et al (2020), andChandra (2023) tried to investigate effects of ATM service quality on customer satisfaction. Various literature revealed that customer satisfaction from the bank sector has been done on ATM service quality and dimension (Al-Azzam, 2015;Aslam et al, 2019).…”
Section: Impact Of Atm Service Quality On Customer Satisfactionmentioning
confidence: 99%
“…A study by Doreen (2013) on service quality and operational performance in tour operators in Kenya found that despite significant level of implementation of various quality components, firms are still unable to attain high operational performance. Onyancha (2013) in his study on effect of bank brand image on customer satisfaction found that customer satisfaction is the key of loyalty intention and that if customers are satisfied, they may create base of loyalty easily. However these studies have failed to address service quality in relation to brand image of logistic firms.…”
Section: Introductionmentioning
confidence: 99%
“…However these studies have failed to address service quality in relation to brand image of logistic firms. Furthermore extant reviewed literature on service quality has focused on commercial banks (Onyancha, 2013;Omolo, 2011). This had left a research gap that needed to be addressed hence the current study examined the effect of service quality on brand image of logistic firms with special focus on logistic companies in Mombasa Island.…”
Section: Introductionmentioning
confidence: 99%
“…Hizmet kalitesinin müşteri bağlılığına doğrudan etkisinin bulunmadığı bu çalışmada müşteri memnuniyeti aracılık rolü ile bu ilişkiyi düzenlemektedir. Ismaıl ve diğerleri (2006), işletmeler üzerinde yaptıkları çalışmada benzer sonuç elde etmişlerdir.Lau ve diğerleri (2013), bankacılık sektörü üzerine yaptıkları çalışmada müşteri memnuniyetinin müşteri bağlılığı ve hizmet kalitesi arasındaki ilişkide aracılık rolü üstlendiğini belirtmişlerdir Nshimiyimana (2020),. ATM gibi hizmet kalite göstergeleri ile müşteri bağlılığı arasındaki ilişkide müşteri memnuniyetinin aracılık rolünü kanıtlamıştır.…”
unclassified